2009
DOI: 10.1111/j.1440-1630.2008.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

From student to therapist: Follow up of a first cohort of Bachelor of Occupational Therapy students

Abstract: Respondents felt adequately prepared to enter the occupational therapy profession and workforce. Strengths and weaknesses in their preparation are discussed as well as the need for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 22 publications
1
41
0
1
Order By: Relevance
“…Undergraduate education has a responsibility to equip students with the knowledge, skills and competencies they need to work as effective entry‐level practitioners (World Federation of Occupational Therapists (WFOT), ). The findings of this study support those of existing literature in that participants valued experiential learning as key in the development of clinical skills and confidence (Doherty et al ., ; Hodgetts et al ., ; Toal‐Sullivan, ). Increased opportunities for experiential learning in curriculum are imperative to the training of occupational therapists.…”
Section: Discussionmentioning
confidence: 97%
“…Undergraduate education has a responsibility to equip students with the knowledge, skills and competencies they need to work as effective entry‐level practitioners (World Federation of Occupational Therapists (WFOT), ). The findings of this study support those of existing literature in that participants valued experiential learning as key in the development of clinical skills and confidence (Doherty et al ., ; Hodgetts et al ., ; Toal‐Sullivan, ). Increased opportunities for experiential learning in curriculum are imperative to the training of occupational therapists.…”
Section: Discussionmentioning
confidence: 97%
“…Participants in this study also reported that they were not confident with a range of technologies relevant to practice, for example using assistive technology, and specialist software or specialist devices. Although this may be unique to this cohort, previous research has also reported a lack of perceived technical skills by occupational therapy graduates (Doherty, Stagnitti & Schoo, ; Robertson & Griffiths, ). West () advocated that universities should teach principles rather than techniques, and knowledge rather than skills.…”
Section: Discussionmentioning
confidence: 99%
“…Practice education is integral to developing and assessing competence for practice as it provides opportunities for students to the following: observe experienced occupational therapists in practice (Vroman, Simmons & Knight, ); plan interventions (Gray et al . ); improve confidence in decision‐making (Doherty, Stagnitti & Schoo, ); and increase self‐awareness and demonstrate competence for practice (Doherty et al .). The current Accreditation standards require that students complete 1000 hours of practice education, including one placement of at least eight weeks duration, in accordance with the guidelines established by the World Federation of Occupational Therapists (WFOT) ().…”
Section: The Importance Of Practice Educationmentioning
confidence: 99%